(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Incidence of diabetes is significantly increasing day by day in last two decades. Around 422 million people were said to be diabetic in 2014 according to a data published by WHO. The prime cause for globally increasing rate of diabetes is the changed lifestyle of the people like sedentary lifestyle, fast foods, junk foods, lack of exercise, mental factors like stress etc. All the patients with increased glycemic index may not be established diabetes. It may be simple Ajeerna, Grahani dosha or Amapradoshaja vikara also. Diabetes is compared with the near similar condition in Ayurveda called as Prameha. Incidence of diabetes is increasing day by day globally. Ayurveda being the oldest medicinal system of the mankind, states this unique condition since the time immemorial. It is said to be one of the Santarpanajanya vyadhi. Even though the explanation of Prameha is found in scattered manner in Brihatrayee and Laghutrayee, here we have considered Charaka samhita as a base to the present article. The aim of article is not to prove Prameha as diabetes or vice versa, instead explain a different approach towards treatment of Prameha based on Hetu (cause), Linga (symptoms) and Aushadha (medicine) triad. It is not important to name a disease, but to treat based on the Dosha vitiated and Samprapti involved